2021
DOI: 10.1088/1475-7516/2021/05/034
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino signal dependence on gamma-ray burst emission mechanism

Abstract: Long duration gamma-ray bursts (GRBs) are among the least understood astrophysical transients powering the high-energy universe. To date, various mechanisms have been proposed to explain the observed electromagnetic GRB emission. In this work, we show that, although different jet models may be equally successful in fitting the observed electromagnetic spectral energy distributions, the neutrino production strongly depends on the adopted emission and dissipation model. To this purpose, we compute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
3

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 162 publications
0
26
1
Order By: Relevance
“…However, association studies of blazars hint toward no excess from the broader population (Aartsen et al 2017). Various other source classes have been proposed as factories of the observed cosmic neutrino flux (Mészáros 2017a;Ahlers & Halzen 2018;Vitagliano et al 2020), such as gamma-ray bursts, cluster of galaxies, star-forming galaxies, and tidal disruption events (TDEs; Tamborra et al 2014;Zandanel et al 2015;Wang & Liu 2016;Mészáros 2017b;Dai & Fang 2017;Lunardini & Winter 2017;Murase 2017;Senno et al 2017;Waxman 2017;Pitik et al 2021). Nevertheless, the neutrino emission from each of these source classes cannot fully account for the observed neutrino flux.…”
Section: Introductionmentioning
confidence: 99%
“…However, association studies of blazars hint toward no excess from the broader population (Aartsen et al 2017). Various other source classes have been proposed as factories of the observed cosmic neutrino flux (Mészáros 2017a;Ahlers & Halzen 2018;Vitagliano et al 2020), such as gamma-ray bursts, cluster of galaxies, star-forming galaxies, and tidal disruption events (TDEs; Tamborra et al 2014;Zandanel et al 2015;Wang & Liu 2016;Mészáros 2017b;Dai & Fang 2017;Lunardini & Winter 2017;Murase 2017;Senno et al 2017;Waxman 2017;Pitik et al 2021). Nevertheless, the neutrino emission from each of these source classes cannot fully account for the observed neutrino flux.…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 10 we also show the predicted neutrino spectra shown in Pitik et al (2021), who computed the neutrino production for a benchmark high-luminosity GRB, among others in the internal shock model , in the internal shock model with dissipative photosphere (IS+PH, Toma et al 2011) and in the proton synchrotron marginally fast cooling model (PSYN, Florou et al 2021;Pitik et al 2021). Because these models were computed for a GRB with a different 𝛾-ray fluence than ours, we appropriately rescaled the neutrino fluence spectra of Pitik et al (2021) for a fair comparison to our results.…”
Section: The Total Neutrino Fluencementioning
confidence: 95%
“…We comment further on the relevant cooling times in the discussion section. The model can be further constrained by the tight constraints from the IceCube (Aartsen et al 2017) and Antares (Albert et al 2017) experiments, as shown by Florou et al (2021) and Pitik et al (2021).…”
Section: Constraining Proton Synchrotron Emission Models By Bethe-hei...mentioning
confidence: 99%